Everything for a dog - M. Martin Ann 1955-; Ann M. Martin (New York : Scholastic, 2010)
In parallel stories, Bone, an orphaned dog, finds and loses a series of homes, Molly, a family pet, helps Charlie through the grief and other after-effects of his brother's death, and lonely Henry pleads for a dog of his own.
O
890